PENGARUH PEMBERIAN PUPUK CAIR ORGANIK LIMBAH JAMUR PADA KOLAM UNTUK MENINGKATKAN PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Haerulan Haerulan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
This study aims to determine whether or not the effect of organic fertilizer in the waste of fungi pools to improve the growth of parrot fish (Oreochromis niloticus). The type of this study was an experimental study using Completely Randomized Design (RAL) with three treatments in control pool (0 ml of fertilizer) P pool (additional 1000 ml of fertilizer) and R pool (additional 500 ml of fertilizer). Then the results of data measurement (length, height, and weight) were analyzed by Analysis of Variance (Anova) with SPSS 16 for windows program. Based on the results of data analysis, it was found that ineffective organic fertilizer application of fungi waste in ponds for growth of parrot fish (Oreochromis niloticus) in control pond (0 ml of fertilizer) pond P (additional 1000 ml of fertilizer) and pond R (additional 500 ml of fertilizer). Fcount test score is 15.453 and Ftable is 3.371 for fish length, then Fcount test is 9.021 and Ftable is 3.371 for fish height, and Fcount 8.815 and Ftable is 3,371 for fish weight. The conclusions from this study indicate that there are three effects of organic mushroom waste on the pond to increase the growth of parrot fish (Oreochromis niloticus).